(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The rapid evelopment of digital technologies has significantly transformed the field of education, particularly in the teaching of English as a Foreign Language (EFL). Online platforms have become an essential tool for teachers and learners worldwide, providing innovative opportunities for language acquisition and communication. These platforms offer flexible learning environments, interactive resources, multimedia materials, and real-time communication that support effective English language learning. The use of online platforms also encourages learner autonomy, increases motivation, and allows students to access educational materials regardless of geographical limitations. This article discusses the major advantages of online platforms in teaching English as a foreign language, focusing on accessibility, interaction, personalized learning, cost-effectiveness, and the development of language skills. Furthermore, it examines the role of teachers in online instruction and highlights the challenges and future prospects of digital language education.